Estudo comparativo entre progressão de feridas de diabéticos e não diabéticos utilizando nova tecnologia de avaliação vulnerária - Mehl, Adriano Antonio (2020)
Introduction: Diabetes mellitus (DM) is the most common endocrine disease and is considered a worldwide epidemic. Among the complications of diabetes is the progressive loss of sensation in the lower limbs, especially in the feet. As a result of these complications, ulcers in insensitive feet can appear, which in many cases, due to the lack of a correct and early evaluation, evolve with serious injuries, contributing to the maintenance of diabetes as the main cause of non-traumatic lower limb amputations. Diabetes is also considered as an important contributing factor for delayed wound healing. Unfavorable developments can be prevented if there is early identification of the risky wound by calculating the wound area and the scar predictive factor. Equipment developed for measuring wounds is still incompatible with our reality, due to technical complexity and high costs. Objective: To facilitate the measurement of diabetic and non-diabetic wounds using a rule developed for this purpose and to establish reliable criteria for the assessment of scar progression. Method: Diabetic and non-diabetic individuals were recruited, who met the inclusion criteria, seeking to establish a comparative analysis between the results obtained by measurements between the 2D-FlexRuler ruler and traditional and computer aided metric modalities. Conclusion: The 2D-FlexRuler ruler is a reliable metric platform for obtaining the anatomical limits of wounds, through manual counting, in a simple way. Manual area estimation with 2D-FlexRuler is more accurate than traditional measurement methods. The use of the percentage rate of reduction of the wound area should be encouraged in the first consecutive weeks of treatment. 2D-FlexRuler allowed the predictive factor for healing to be achieved two weeks early, which contributes to the best therapeutic result and the lowest rate of complications, especially in diabetics.